Preclinical x-ray dark-field imaging: Foreign body detection - Braig, Eva-Maria; Muenzel, Daniela; Fingerle, Alexander; Herzen, Julia; Rummeny, Ernst; Pfeiffer, Franz; Noer, Peter (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2017)
The purpose of this study was to evaluate the performance of X-ray dark-field imaging for detection of retained foreign bodies in ex-vivo hands and feet. X-ray dark-field imaging, acquired with a three-grating Talbot-Lau interferometer, has proven to provide access to sub-resolution structures due to small-angle scattering. The study was institutional review board (IRB) approved. Foreign body parts included pieces of wood and metal which were placed in a formalin fixated human ex-vivo hand. The samples were imaged with a grating-based interferometer consisting of a standard microfocus X-ray tube (60 kVp, 100 W) and a Varian 2520-DX detector (pixel size: 127 μm). The attenuation and the dark-field signals provide complementary diagnostic information for this clinical task. With regard to detecting of wooden objects, which are clinically the most relevant, only the dark-field image revealed the locations. The signal is especially strong for dry wood which in comparison is poorly to non-visible in computed tomography. The detection of high atomic-number or dense material and wood-like or porous materials in a single X-ray scan is enabled by the simultaneous acquisition of the conventional attenuation and dark-field signal. Our results reveal that with this approach one can reach a significantly improved sensitivity for detection of foreign bodies, while an easy implementation into the clinical arena is becoming feasible.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Foreign body detection; Talbot grating interferometry; X-ray dark-field